Novel bonding technology for hermetically sealed silicon micropackage - Lee, DJ; Ju, BK; Choi, WB; Jeong, JW; Lee, YH; Jang, J; Lee, KB; Oh, MH (JAPAN J APPLIED PHYSICS, 1999)
We performed glass-to-silicon bonding and fabricated a hermetically sealed silicon wafer using silicon direct bonding followed by anodic bonding (SDAB). The hydrophilized glass and silicon wafers in solution were dried and initially bonded in atmosphere as in the silicon direct bonding (SDB) process, but annealing at high temperature was not performed. Anodic bonding was subsequently carried out for the initially bonded specimens. Then the wafer pairs bonded by the SDAB method were different from those bonded by the anodic bonding process only. The effects of the bonding process on the bonded area and tensile strength were investigated as functions of bonding temperature and voltage. Using scanning electron microscopy (SEM), the cross-sectional view of the bonded interface region was observed. In order to investigate the migration of the sodium ions in the bonding process, the concentration of the bonded glass was compared with that of standard glass. The specimen bonded using the SDAB process had higher efficiency than that using the anodic bonding process only.